Oral Health Literacy and Measures of Periodontal Disease - Holtzman, Jennifer S. (J Periodontol, 2016)
BACKGROUND: Existing evidence demonstrating a relationship between health literacy (HL) and periodontal health is insufficient to identify how providers can help patients manage periodontal disease. This study assesses associations between HL measures (word recognition, numeracy, and conceptual knowledge) and signs of periodontal disease. METHODS: This study included 325 new patients at a dental school clinic and employed an oral HL (OHL) survey, full-mouth radiographs, and clinical examination. Evaluations included the relationship between each HL measure versus number of teeth, bleeding score, plaque score, and periodontal severity with linear and ordinal logistic regression models before and after adjusting for covariates. RESULTS: Among HL measures, the Newest Vital Sign demonstrated a significant relationship with number of teeth and the Short Test of Functional Health Literacy in Adults showed a significant association with plaque score. The short Rapid Estimate of Adult Literacy in Medicine and Dentistry (REALMD-20) showed participants who performed in the highest quartile had nearly two additional teeth, over 5.5% fewer bleeding sites, and nearly 9% fewer teeth with plaque after adjustment for demographic variables, smoking, and diabetes mellitus (DM). Participants who scored in the highest quartile of the Comprehensive Measure of Oral Health Knowledge (CMOHK) had nearly 9% less plaque. CONCLUSIONS: Two OHL instruments (REAMLD-20 and CMOHK) provided statistical associations with clinical measures of periodontal health at a level that could be considered of moderate clinical relevancy. Findings suggest dentists may wish to assess familiarity of their patients with dental terminology and knowledge of periodontal disease to provide education on oral hygiene, smoking, and DM.